History of Pain Research and Management in Canada - Harold Merskey (Pain Research and Management)
Scattered accounts of the treatment of pain by aboriginal Canadians are found in the journals of the early explorers and missionaries. French and English settlers brought with them the remedies of their home countries. The growth of medicine through the 18th and 19th centuries, particularly in Europe, was mirrored in the practice and treatment methods of Canadians and Americans. In the 19th century, while Americans learned about causalgia and the pain of wounds, Canadian insurrections were much less devastating than the United States Civil War. By the end of that century, a Canadian professor working in the United States, Sir William Osler, was responsible for a standard textbook of medicine with a variety of treatments for painful illnesses. Yet pain did not figure in the index of that book. The modern period in pain research and management can probably be dated to the 20 years before the founding of the International Association for the Study of Pain. Pride of place belongs to The management of pain by John Bonica, published in Philadelphia in 1953 and based upon his work in Tacoma and Seattle. Ideas about pain were evolving in Canada in the 1950s with Donald Hebb, Professor of Psychology at McGill University in Montreal, corresponding with the leading American neurophysiologist, George H Bishop. Hebb's pupil Ronald Melzack engaged in studies of early experiences in relation to pain and, joining with Patrick Wall at Massachusetts Institute of Technology, published the 1965 paper in Science that revolutionized thinking. Partly because of this early start with prominent figures and partly because of its social system in the organization of medicine, Canada became a centre for a number of aspects of pain research and management, ranging from pain clinics in Halifax, Kingston and Saskatoon - which were among the earliest to advance treatment of pain - to studying the effects of implanted electrodes for neurosurgery. Work in Toronto by Moldofsky and Smythe was probably responsible for turning ideas about fibromyalgia from the quaint concept of 'psychogenic rheumatism' into the more fruitful avenue of empirical exploration of brain function, muscle tender points and clinical definition of disease. Tasker and others in Toronto made important advances in the neurophysiology of nociception by the thalamus and cingulate regions. Their work continues while a variety of basic and clinical studies are advancing knowledge of fundamental mechanisms, including work by Henry and by Sawynok on purines; by Salter and by Coderre on spinal cord mechanisms and plasticity; by Katz on postoperative pain; by several workers on children's pain; and by Bushnell and others in Montreal on cerebral imaging. Such contributions reflect work done in a country that would not want to claim that its efforts are unique, but would hope to be seen as maintaining some of the best standards in the developed world.